KINERJA KEUANGAN DAERAH PEMEKARAN DITINJAU DARI RASIO DAN INDEKS KEUANGAN - Yusron Difinubun; Muhammad Gudono (Program Studi Akuntansi Unimuda Sorong, 2021)
This study comes from asymmetrical condition between the high failure of the implementation of the new autonomous region, since there is unnatural process and high willingness in doing regional expansion. The research aims to obtain empirical evidence concerning the financial performance of the district and the regional expansion of Maluku Province, to help reducing the high failure of the regional expansion of Maluku Province and other district generally in Indonesia, by minimizing the decline causes of the local financial performance. The measurement of financial performance of the district/ the regional expansion of Maluku Province use ten indicators of financial performance, such as the ratio of fiscal decentralization degree, the ratio of financial capacity, the ratio of financial independence, the ratio of PAD effectiveness, the degree of BUMD contribution, the activity ratio (routine expenditure and investment expenditure), the ratio of effectiveness and the efficiency of expenditure, and financial capability index. This study uses a qualitative method and two data collection techniques, as well as two data analysis. The first is by collecting book secondary data I LHP BPK on LKPD district/ the regional expansion of Maluku Province